Investigation of Apparatus Reliability Applied for Protection of Power Networks in Emergency Operational Cases at Dwelling Sector of the Republic of Belarus - G. T. Kulakov; A. N. Kukharenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
On the basis of statistic data analysis it has been established that nearly 10 % of fires that occurred in the dwelling sector of the Republic of Belarus in 2006 are related with emergency regime of electric equipment, electric devices and power networks. The paper contains results of experimental comparative investigations concerning operation of fuses for 25 A current and automatic thread fuses for nominal 25 A current.The investigations have shown that fuses do not ensure protection of power networks in a dwelling in 40 % of executed tests. Replacement of these fuses for automatic thread ones permits to reduce a number of fires in a dwelling sector and, first of all, in the rural area.